Uniformidade da fertirrigação em um sistema de irrigação por gotejamento. - Magalhães, Maria Izali (1996)
This research was developed with the objective of evaluating the Phosphorus (P) and Potassium (K) distribution by a drip irrigation system, and their movement into the soil profile limited by the wet zone. In the study of the fertilizer distribution uniformity in the manifold line, it was chosen the first emitter of the two extreme lines, and the first emitter of the two intermediate lines, and to study the fertilizer distribution by the lateral line, were chosen the two extreme and the two intermediate dripperss from the lateral line with best uniformity. The water sampling started as the fertilizer was introduced into the system and lasted 90 min. The time that the solution reached the emitters was found through a portables Electric Conductivity gauge. Than, the samples were collected minute-by-minute in the lateral line, and in five-minute interval in the manifold line. The chemical parameters used in the evaluation of the fertilizer distribution, were the Electrical Conductivity (EC), pH, P and K rate. Analyzing the fertilizer distribution through the drip line, admitting constant flow rate of the emitters, it was found that the differences in the amount of fertilizer applied were 2,4%; 4,2% and 8,1% for P and 2,6%; 3,1% and 3,6% for K, respectively in the 2º, 3° and 4° emitter in the line, in relation to the first emitter, what indicate a little decrease in the nutrient applied from the beginning to the end of the line, specialIy considering Phosphorus. In addition, analyzing the distribution of fertilizers applied by a system working at two different uniformity of water application (100% e 96,4%), it was found that the uniformity of distribution of fertilizer is largely affected the distribution of water. It was also found that the Electrical Conductivity of the irrigation water is a useful parameter in the evaluation of the fertilizer distribution. The Results of the fertilizer distribution into the soil profile show that the Phosphorus applied reached a radius of 15 cm, and the Potassium reached a radius larger than 40 cm.